KONSEP PEMIKIRAN PENDIDIKAN ISLAM KH. HASYIM ASY’ARI DAN SYAIKH AHMAD KHATIB AL-SAMBASI - Rahamad Ari Wibowo (Tarbawiyah Jurnal Ilmiah Pendidikan, 2018)
This paper reviews the concept of Islamic education thinking Hasyim Ash'ari which explains about how the rules of teaching and learning that emphasizes the ethical aspects of learning. The concept of Islamic education Hasyim Ash'ari is one of the bids in overcoming the spiritual crisis in the world of education today. Hasyim Asy'ari's educational thought does have high spiritual values ​​of Sufism. This is due, Hasyim Asy'ari put tasawuf as the foundation of education in shaping the character of learners who berakhlatul karimah and intlektual. The concept of Islamic education Hayim Ash'ari, if associated with the Concept of Sufism Ahmad Khatib Al-Sambasi not only complement each other but strengthen the theory of Islamic education Hasyim Asy'ari. Hashim Asy'ari's education theory is very relevant in shaping the character of learners in their morals, intellectual and spirituality in this modern era. Modern education today, tends to emphasize the cognitive aspect although in educational theory there are elements of cognitive, affective and psychomotor aspects. This is what resulted in the lack of "blessing" knowledge of learners in gaining knowledge. One of the most important parts to be considered and emphasized in addition to the cognitive aspect is the affective aspect (spirituality and ethics) in the teaching and learning process, whether as a teacher or pupil in education. It is time for education to focus on affective aspects (moral, ethical and spiritual). Spiritual, ethical and moral crises are an important study in the world of education, especially Islamic-based education.